Les syndicats français et américains face aux mutations technologiques. - Dommergues, Pierre; Plantu; Groux, Guy; Mason, John; Julien, Claude; Harrington, Michael (Paris : Anthropos, 1984)
Bibliotheek François Vercammen
Frans
Monografie